Sistemas rotatórios ProTaper Next, X File e X Gray: características e desempenho no preparo de incisivos inferiores - Oliveira, Kauhanna Vianna de (2020)
The constant evolution of rotating instruments optimizes endodontic therapy, promoting facility for the dentist, comfort and safety for the patient. The automation of chemicalmechanical preparation has become usual, accompanying the new techniques and materials development, which are the subject of important studies for clinical practice. Therefore, the general proposition of this thesis was to study the X File (XF) and X Gray (XG) rotary systems - (TDK – Shenzhen Superline Technology, Shenzhen, China) comparing their performance with the ProTaper Next (PTN) system - (Dentsply Sirona, Ballaigues, Switzerland), through two articles. The first one aim was to evaluate maintenance of channel position, volume variation and untouched areas for the three systems. Forty-five lower incisors were divided into three groups according to the system: PTN (n=15), XF (n=15) and XG (n=15). A pre-instrumentation (PI) computerized microtomography (micro-CT) was performed by which the teeth were classified into round, oval, long oval or flat shape. After each instrument use X1 (0.17/.04), X2 (0.25/.06) and X3 (0.30/.07), other micro-CT exams were performed. For statistical analysis, the Kolmogorov-Smirnov normality test evaluated each sample, general comparisons for non-normal data were performed with Kruskal-Wallis and Mann-Whitney test for paired comparisons (transport and centralization). Data with normal distribution were evaluated by using the tests One-Way ANOVA (percentage of non-instrumented areas) or Two-Way ANOVA (volume variation). If there was a significant difference for normal data, the tests Tukey HSD (homogeneous variance) or Games-Howell (heterogeneous variance) was used. The confidence interval was 95% and the test power was superior than 99%, when it indicated a significant difference. The volume variation presented a significant difference for the third factor, the cervical had a higher average value than medium (p<0.001), and both were larger than apical (p<0.001). There was a statistically significant difference between PI and the X3 instruments for the PTN (p = 0.006), XF (p = 0.046) and XG (p = 0.0200) systems. However, there was no significant difference regarding the systems used (PTN, XF and XG) (p>0.05). The analysis of untouched walls percentage did not indicate a significant difference between the systems (p=0.836). Related to transport, the results were similar for the third (p=0.721), but there was a significant difference according to the system (p=0.049), PTN generated a superior transport degree than XF (p=0.031) and XG (p=0.037). Centralization presented no difference between studied systems (p=0.369), but there was variation between the thirds (p<0.001), the medium exhibited a higher degree of centralization than the cervical (p=0.009) and t he apical third (p=0.031). It was concluded that the PTN, XF and XG systems behaved similarly according to the dentin wear capacity, percentage of non-instrumented walls and centralization, however the transport degree was higher for PTN than XF and XG. The second article aimed to evaluate the resistance to cyclic fatigue of the X File (XF), X Gray (XG) and ProTaper Next (PTN) rotary systems. There were used instruments X2 (25/.06) of systems PTN (n=18), XF (n=18) and XG (n=18), the instruments were inserted in the X Smart IQ motor contra-angle (Dentsply Sirona, Ballaigues, Switzerland) coupled to the dynamic cyclic fatigue test device. There were standardized the speed of 300 rpm and torque of 3 Ncm. Each instrument was activated until fracture and the time recorded on a digital timer. The fragment resulting from each fracture was measured with a digital caliper. Data related to time and NCF variables were analyzed by using the Kruskal-Wallis test for general comparisons, and Mann-Whitney for paired comparisons. The fragment variable was evaluated by the One-Way ANOVA test with a 95% confidence interval. The XG system presented values of resistance to cyclic fatigue significantly higher than PTN and XF (p<0.001). The average length of fractured fragments exhibited no significant difference between the groups (p=0.138). It was concluded that the XG system presented superior resistance to cyclic fatigue fracture compared to PTN and XF, however there was no difference between the fragments in all systems.